Comprehensive characterization and identification of chemical constituents of Pingwei Powder by ultra high performance liquid chromatography tandem quadrupole-time-of-flight tandem mass spectrometry - Tongyan Zhu; Na Li; Chunying Zhao; Jianwei Liu; Yuling Liu; Jianhui Chen; Yuxin Dong; Yuxuan Tian; Xia Hong; Hui Xiong (Journal of Chromatography Open)
Pingwei Powder, a basic traditional Chinese medicine (TCM) prescription, was used for treating the chronic colitis, liver cirrhosis, and acute gastritis, etc. However, its systematic chemical characteristics has not been reported, which hinders the interpretation of its therapeutic mechanism, and quality control.To develop a powerful ultra high performance liquid chromatography tandem quadrupole-time-of-flight tandem mass spectrometry (UHPLC-Q-TOF-MS)-based method for the systematic chemical characterisation of Pingwei Powder, providing a basis for further research on pharmacological substance basis, and quality control of Pingwei Powder. UHPLC-Q-TOF-MS was used to detect a wide range of chemical substances in Pingwei Powder, and the obtained spectral data were imported into PeakView 1.2 software for data processing. Subsequently, the chemical substances in Pingwei Powder were identified by comparison with reference standards, literatures, and the built-in database of SCIEX OS 2.2 software. Finally, the chemical profile of Pingwei Powder was acquired, and 329 chemical components in Pingwei Powder were identified for the first time, mainly including flavonoids, terpenoids, organic acids, alkaloids, phenylpropanoids. Of note, 48 were from Atractylodis Rhizoma, 37 were from Magnoliae Officinalis Cortex, 72 were from Citri Reticulatae Pericarpium, 80 were from Glycyrrhizae Radix et Rhizoma, 32 were from Ginger, 60 were from Ziziphus jujuba. A scientifically efficient and credible method for obtaining the comprehensive chemical profile of Pingwei Powder based on UHPLC-Q-TOF-MS was developed for the first time, providing a basis for further research on pharmacological substance basis, and quality control of Pingwei Powder.